Selected poems - Pratt, E. J. (Edwin John), 1882-1964.; Djwa, Sandra, 1939-; Keith, W. J. (William John), 1934-; Pollock, Zailig (Toronto, Ont. : University of Toronto Press, 2000)
The purpose of The Selected Poems of E.J. Pratt is to introduce Pratt's poems to the college and university student, to provide the kind of information needed for an informed reading of the poems. The volume offers a full sampling of Pratt's poems chosen on the joint basis of representativeness and intrinsic value. This includes the major long poems, The Witches' Brew, The Iron Door, The Titanic, BrTbeuf and His Brethren, Towards the Last Spike, and important shorter lyrics including 'Newfoundland, ' 'Come Away, Death, ' and 'From Stone to Steel.'The editorial approach has been historical, chronological and biographical. The introduction locates Pratt in his Newfoundland and Canadian contexts and discusses the development of his work in terms of his early modernist contemporaries, concluding that E.J. Pratt remains the most important and influential Canadian poet up to the mid-fifties. As such, he has been an key figure in shaping the Canadian literary imagination of his day and the later poetics of landscape adopted by Earle Birney and Margaret Atwood.The reader is provided with annotations, textual notes, a biographical chronology, and an introduction which locates Pratt in his Newfoundland and Canadian contexts and discusses the development of his work in terms of his modernist contemporaries. The printed volumes is supplemented by the electronic resources of the Selected Pratt website at http://www.trentu.ca/pratt/selected.
The Good EarthTowards the Last Spike -- NOTES -- SELECTED BIBLIOGRAPHY -- INDEX OF TITLES -- INDEX OF FIRST LINES
Includes bibliographical references (pages 237-239) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Canada -- Poetry; Canada -- Poésie.; POETRY -- Canadian; FICTION -- General; Canada; Electronic books; e-books.; Poetry; Livres numériques.